2021
DOI: 10.1371/journal.pone.0251789
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different models of sucrose intake on the oxidative status of the uterus and ovary of rats

Abstract: The aim of the study was to assess the effect of different models of sucrose intake on carbohydrate-lipid metabolism and changes in oxidant balance in the ovaries and uterus of rats. Animals were divided into three groups: I—basic feed, II—feed contains 8% of sucrose, III—alternately every second week the basic feed and modified feed contains 16% of sucrose. The diet containing 8% of sucrose was found to result in an increased activity of antioxidant enzymes in the blood, with unchanged malonylodialdehyde conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Abundant clinical studies have confirmed that a high-sugar diet can lead to an OS state in the body, which accelerates the development of multisystem pathologies, such as diabetes, neurodegenerative and cardiovascular diseases [108][109][110]. A high-sugar diet, whether long-term, short-term or fluctuating, can affect the body's redox status and thus have a negative impact on ovarian function [111].…”
Section: High-sugar Dietmentioning
confidence: 99%
“…Abundant clinical studies have confirmed that a high-sugar diet can lead to an OS state in the body, which accelerates the development of multisystem pathologies, such as diabetes, neurodegenerative and cardiovascular diseases [108][109][110]. A high-sugar diet, whether long-term, short-term or fluctuating, can affect the body's redox status and thus have a negative impact on ovarian function [111].…”
Section: High-sugar Dietmentioning
confidence: 99%
“…That high-sucrose diets reduce LH levels suggests that the effect may be due to, inter alia, factors related to the profile of metabolic disorders that accompany sucrose consumption. We have already shown [ 19 , 20 ] that a high-sucrose diet (HSG and PSG), even when administered periodically (AFG), significantly increases glycemia, the HOMA-IR index, and LDL-cholesterol, and reduces the HDL-cholesterol concentration as compared to the group fed a low-sucrose diet (SBG).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, insulin resistance is strongly associated with lower levels of HDL-cholesterol, which modulates glucose metabolism by activating AMP-dependent protein kinase (AMPK) [ 45 ]. Hence, both insulin resistance and the low HDL-cholesterol levels shown in our previous studies in the HSG, AFG, and PSG [ 19 , 20 ] may have contributed to the disruption of the hypothalamic–pituitary axis, including the reduction in LH synthesis and/or secretion [ 46 ]. Insulin is a signal that links metabolism with reproduction, particularly since Kiss1 neurons are sensitive to circulating metabolic signals such as leptin and insulin, which confirms their importance in mediating the body’s response to nutrition or malnutrition [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations